Recurrent Obscure Gastrointestinal Bleeding: Dilemmas and Success with Pharmacological Therapies. Case Series and Review - Majid Almadi; Peter M Ghali; Andre Constantin; Jacques Galipeau; Andrew Szilagyi (Canadian Journal of Gastroenterology)
The present article describes three difficult cases of recurrent bleeding from obscure causes, followed by a review of the pitfalls and pharmacological management of obscure gastrointestinal bleeding. All three patients underwent multiple investigations. An intervening complicating diagnosis or antiplatelet drugs may have compounded long-term bleeding in two of the cases. A bleeding angiodysplasia was confirmed in one case but was aggravated by the need for anticoagulation. After multiple transfusions and several attempts at endoscopic management in some cases, long-acting octreotide was associated with decreased transfusion requirements and increased hemoglobin levels in all three cases, although other factors may have contributed in some. In the third case, however, the addition of low-dose thalidomide stopped bleeding for a period of at least 23 months.